2014
DOI: 10.1186/1471-2407-14-370
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid sensitizes pancreatic cancer cells to natural killer cell-mediated lysis by upregulating MICA and MICB via the PI3K/Akt signaling pathway

Abstract: BackgroundValproic acid (VPA), a histone deacetylase (HDAC) inhibitor, is reported to exert anti-tumor effects by upregulating the expression of the natural killer group 2D (NKG2D) ligands on tumor cells; however, the mechanisms vary in different tumor types, and the effect and mechanism of action of VPA in pancreatic cancer cells are unknown.MethodsThe present study evaluated the effect of VPA to susceptibility of pancreatic cancer cells to the NK cell-mediated lysis in vitro and in vivo. Then we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 40 publications
0
47
0
Order By: Relevance
“…Considering that a variety of aliphatic acid compounds have been reported to inhibit histone deacetylase [54,55], we found that 8-HOA could also act as a histone deacetylase inhibitor (Fig. 1C).…”
Section: Discussionmentioning
confidence: 90%
“…Considering that a variety of aliphatic acid compounds have been reported to inhibit histone deacetylase [54,55], we found that 8-HOA could also act as a histone deacetylase inhibitor (Fig. 1C).…”
Section: Discussionmentioning
confidence: 90%
“…Various studies have suggested the involvement of multiple signaling pathways in the development, progression and metastasis of pancreatic cancer (30-37). One such pathway, Notch1 signaling, a highly conserved pathway throughout the animal kingdom, plays an important role in cellular differentiation, proliferation, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage has been implicated in the induction of NKG2D ligands via DNA damage response ATM and ATR pathway [33]. Post-transcriptional epigenetic modifications with histone deacetylase (HDAC) inhibitors along with DNA damaging low-dose chemotherapy or radiotherapy can upregulate MICA/B expression in an array of human tumor cells [34,35 ●● ,3639,40 ● ,41 ●● ]. Expression of MICA/B and ULBP3 can also be regulated by endogenous microRNAs [4244].…”
Section: Nkg2d Ligands In Human Cancermentioning
confidence: 99%